"Induced-Fit Suction" effect: a booster for biofuel storage and separation. Issue 39 (23rd September 2019) - Li, He; Guo, Fangyuan; Hu, Jun; Peng, Changjun; Wang, Hualin; Liu, Honglai; Li, Jing
Abstract : An "Induced-Fit Suction" effect was proposed by fine-tuning the amphiphilicity of ZIF-7 and facilitated the selective adsorption of n -butanol from aqueous solution through structural deformation. Abstract : Target-response deformation has provided a wide variety of possibilities for selective molecular separation. In this report, both experimental and theoretical methods were used to demonstrate how fine-tuning the amphiphilicity of ZIF-7 can induce an alcohol-based target-response deformation. A step-by-step simulation of dynamic adsorption revealed that ZIF-7-NH2 can successfully align alcohol molecules to facilitate selective adsorption, while the benzene rings in ZIF-7-NH2 were induced to flip over and maintain the open-gate conformation. As a result, ZIF-7-NH2 with an amino mole ratio of 10% achieved an ideal n -butanol/water selectivity of 40, and also the highest n -butanol uptake of 4.33 mmol g −1 from 5 wt% n -butanol aqueous solution under ambient conditions. Therefore, a new mechanism of "Induced-Fit Suction" (IFS) that we propose provides a promising new strategy for biofuel separation.